Assessing attentional bias for alcohol-related cues using eye tracking in a virtual reality environment - Simon, Jessica; Grogna, David; Rivard, Marie-Christine; Heck, Michelle; Bouchard, Stéphane; Quertemont, Etienne (Frontiers in Virtual Reality, 2022)
Several experimental paradigms were developed to measure attentional biases towards alcohol-related cues. However, most of them are based on reaction times to two-dimensional stimuli displayed on a computer screen, such that their ecological validity has been questioned. To address this, we integrated an eye tracking system into a virtual reality headset (ET-VR) and measured attentional biases in a subclinical population of alcohol users. In this exploratory study, forty social drinkers were recruited and immersed in a virtual bar including alcohol-related stimuli. Attentional focus was assessed using dwell time and number of fixations for these alcohol-related stimuli as well as for neutral stimuli unrelated to alcohol consumption. The results show that the number of fixations and, to a lesser extent, the dwell time for alcohol-related cues were positively correlated with the drinking motivation of the participants. In contrast, no significant correlation was found for neutral stimuli. In conclusion, the present study shows that alcohol-induced attentional biases can be studied using an ET-VR device in a subclinical population of alcohol users.